Naẓariyah al-Qiyādah al-Ḥadīṡah: Dirāsah Tafsīriyyah Muqāranah baina al-Ᾱyāt al-Qur’āniyyah wa al-Naẓriyyāt al-Mu‘āṣirah - Hoxha, Hajredin (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2021)
This study aims to deeply analyze the theory of modern leadership from the perspective of Qur'anic verses and compare them with contemporary studies. In this study, the researcher followed the descriptive, analytical, and comparative approaches. The problem of this study revolves around explaining the inability of Western studies to solve the problem of leadership due to its narrow view of the science of leadership and its various dimensions. For them, the leadership is purely institutional, local, and worldly issues! Unfortunately, it was noticed that some Muslims were impressed negatively by these studies. This study comes to refute those allegations and to show them that the Noble Qur’an has provided us with the principles of local and global leadership in its various surahs and verses through the personalities of the prophets, messengers, kings, and other people in different eras and regions. This study proved that contemporary studies, despite their abundance and diversity; It did not bring anything new more than what the Holy Qur’an had brought about fourteen centuries ago. This study was divided into an introduction, two chapters, and a conclusion. In the first chapter, I mentioned the theories and approaches of modern leadership, then in the second chapter, I commented on the alternative Qur’anic perspective on the science of successful leadership, with its conclusion and recommendations.